Experience of bisphosphonate related osteonecrosis of the jaw treatment in patient with chronic periodontitis of mandibular teeth (case review) (LLC "Endo Press", 2020)
Osteonecrosis of the jaw is one of the complications which developes in patients receiving bisphosphonates therapy after invasive dental procedures. Bisphosphonate therapy applied in treatment of patients with osteoporosis (in oral form), as well as in the treatment of patients with malignant diseases with metastatic bone lesions (intravenous drugs). At the moment there is no consensus on treatment strategies for this complication is offered as a conservative and surgical treatment protocols. The number of patients who developed this complication increases every year, due to the widespread introduction of these drugs in medical practice. The actual problem is early diagnosis and choice of optimal treatment strategies, ensuring a higher quality of life for the patient and the prevention of complications.